Peranan Jargon pada Iklan Minuman Ringan Teh Botol Sosro - Jhonny Syahkuan; Syarifah Nimah; Malik Abdul Azis; Asman Aminudin Bakri; Sayid Mochhamad Ulil Absor (CV. Publikasi Indonesia, 2022)
Jargon is a special thing that can be used in a limited way in the field of knowledge or certain circles where they themselves know what it means and what it means. An ad editorial is certainly required not to use unique or difficult to understand words in making jargon. The purpose of the study was to determine the role of Jargon in the advertisement for soft drink tea Botol Sosro which reads